UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL BIJI BUAH NYIRIH (Xylocarpus granatum) DENGAN METODE DPPH SECARA SPEKTROFOTOMETRI UV-VIS - Achmad Kadri Ansyori; Mutmainna Tamrin; Hayatus Sa'adah (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
The nyirih plant (Xylocarpus granatum) is a type of mangrove that has been used for generations by coastal communities as traditional medicine. The flavonoid compounds contained in the nyirih plant are a group of polyphenols which have potential as antioxidants that can reduce free radicals. The aim of this research was to determine the antioxidant activity of ethanol extract of nyirih fruit seeds. The research carried out was non-experimental research, the stages of this research started from plant determination and sample collection, making simplicia, making extracts using the maceration method with 70% ethanol, phytochemical screening, and antioxidant activity testing using the DPPH method as free radicals which were measured using a spectrophotometer. UV-Vis. The research results obtained showed that the ethanol extract of nyirih fruit seeds positively contained secondary metabolites in the form of alkaloids, flavonoids, tannins and saponins. The results of the antioxidant activity test of the ethanol extract of nyirih fruit seeds obtained an IC50 value of 8.2729 ppm in the very strong antioxidant category.